A verbo-visualidade no conto A lenda da cobra grande: adaptação e tradução - Frutuoso, Aline de Fátima da Silva Araújo (2023)
This dissertation presents the analysis of meaning guided by the theoretical category of verbalvisuality in the light of Bakhtin's precepts. The general objective of this study was to identify the process of production of meanings in the verb-visual works: Lenda da Cobra Grande (2013 translation) and A Cobra Grande (2016 adaptation). The specific objectives were: to verify, in the works, the presence of verbal-visuality and elements related to deaf culture; demonstrate how the expression of the senses is made in the elements that make up each work (illustrations, the verbal in Portuguese and written and signed Libras); observe the historical-cultural relations and how they dialogue in the attribution of meanings; describe the similarities and differences in the production of meanings between the translation of “Lenda da Cobra Grande” and the adaptation of “A Cobra Grande”. These works bring the cultural aspects of two Brazilian minorities - the original peoples and the deaf people as a minority in Brazilian society. The methodological path was qualitative, with an exploratory and documentary research. The corpus analyzed was composed of verbal-visual texts in the translation bias and other literary productions. As a technique for analyzing the meaning of verbal-visual texts, pairs and trios of pages were used, inferring some of Bakhtin's categories such as authorship, ideology, heterodiscourse, meaning and theme. In the results, we found similarities and differences in the production of meaning between Lenda da Cobra Grande and A Cobra Grande. The presence of dialogic elements was verified through the existing discourse, and ideological ones, materialized in the evaluative and axiological positions of the characters based on the sociohistorical context. In translation, a verbal-visual work, we have the presence of dialogical relationships, authorship and ideology. In the adaptation, we have the heterodiscourse that corresponds to the voices, to the authorship (the author-person and author-creator), as well as the ideology with evaluative positions, evoking voices of the deaf community. Dialogue emerges from the main character's contact with his community and language, refracting significant values.